Economics of capital adjustment in the US commercial banks: Empirical analysis - Faisal Abbas; Shoaib Ali; Ghulame Rubbaniy (Journal of Applied Economics, 2021)
Using GMM framework on the data of the US commercial banks spanning over 2002 to 2018, this study shows that banks adjust their regulatory capital ratios faster than traditional capital ratios. Our results show that the speed of adjustment of regulatory capital ratios and traditional capital ratios increases in bank capital adequacy and bank liquidity, respectively. We also find that the speed of adjustment of regulatory capital ratios of too-big-to-fail banks is lower than well-capitalized, adequately-capitalized, nationally-chartered, and state-chartered banks. In addition, the speed of adjustment of regulatory capital ratios of commercial banks is higher in the post-crisis period than the pre-crisis era. Although scholars suggest that adjustment of capital ratios through rebalancing liabilities is more beneficial to the banks, our findings show that banks also use their assets side of balance sheet to rebalance their capital ratios.
Keywords: 330; Capital ratio; regulatory ratio; tier-I ratio; speed of capital adjustment; bank charters